2011
DOI: 10.1248/bpb.34.433
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance Protein 2 Implicates Anticancer Drug-Resistance to Sorafenib

Abstract: Sorafenib and sunitinib is a small molecule inhibitor of certain receptor tyrosine kinases, and have improved outcomes for patients with advanced renal cell carcinoma. Inhibitory concentration of 50% cell growth of sorafenib significantly rose to 6.4-fold in a multidrug resistance protein 2 (MRP2) transfected cell line versus control cell line. The concentration of sorafenib was significantly decreased to 74% of control cells after 3 h treatment. In contrast, a tyrosine kinase inhibitor sunitinib did not show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 16 publications
3
39
0
Order By: Relevance
“…In addition to the above described mechanisms, some limited studies have also demonstrated that EGFR [10] , glucose-regulated protein 78 (GRP78) [41] , multidrug resistance protein (MDRP) 2 [42] , nuclear factor κB (NF-κB) [43,44] and autophagy [45] may be involved in the acquired resistance to sorafenib in HCC.…”
Section: Hypoxic Microenvironment and Sorafenib Resistancementioning
confidence: 99%
“…In addition to the above described mechanisms, some limited studies have also demonstrated that EGFR [10] , glucose-regulated protein 78 (GRP78) [41] , multidrug resistance protein (MDRP) 2 [42] , nuclear factor κB (NF-κB) [43,44] and autophagy [45] may be involved in the acquired resistance to sorafenib in HCC.…”
Section: Hypoxic Microenvironment and Sorafenib Resistancementioning
confidence: 99%
“…The two inhibitors show significant activity against neovascularization-related RTKs, such as VEGFR2, VEGFR3, and PDGFR-β (23,24). Although one of the most noteworthy target kinases of sorafenib is Raf-1, the contribution of the Raf kinase inhibitory properties of sorafenib to the antitumor effect in RCC is not completely understood (1).…”
Section: A B C D Ementioning
confidence: 99%
“…One of the main causes of the MDR phenotype is the overexpression of P-glycoprotein, encoded by the multidrug resistance gene (MDR1) and multidrug resistance-associated proteins (MRP) (23). Findings of a recent study have shown that of the two MKIs, only sorafenib is a substrate for MRP2, a clinically significant member of the MRP transporter family (24). In addition, MRP2 is known to be linked to resistance against 5FU (25).…”
Section: A B C D Ementioning
confidence: 99%
“…25 The cellular efflux mechanisms of sorafenib and nilotinib have been reported in various studies and involved breast cancer resistance protein (BCRP), P-glycoprotein (P-gp), and multidrug resistance protein (MRP)-2 for sorafenib only. [60][61][62][63] Interestingly, while there is no basal expression of P-gp reported in these cell lines, treatment with a chemotherapeutic agent may induce …”
mentioning
confidence: 91%